Comparison of center of mass energy fluctuations by use of force and motion capture recordings - Ettema, G.; Danielsen, J.; Sandbakk, O. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Recent studies have investigated the mechanical energy (ME) fluctuations of the center of mass (CoM) in cross-country (XC) skiing techniques (1,2). The most used method of CoM ME calculation in human movement is by use of force platforms to record ground reaction forces (GRF). This method, however, fails to include the rotational component of the kinetic energy (Ekin-r), which arguably is important in XC skiing, especially in double poling (DP). The present study compared the use of force platforms to that of the sum of segmental energy calculations, both with and without Ekin-r.